Scorpionism by Tityus silvestris in eastern Brazilian Amazon - Johne Souza Coelho; Edna Aoba Yassui Ishikawa; Paulo Roberto Silva Garcez dos Santos; Pedro Pereira de Oliveira Pardal (Journal of Venomous Animals and Toxins including Tropical Diseases, 2016)
Abstract Background Scorpionism is a serious public health problem in Brazil. Although cases of envenomation by scorpions are frequent in Brazil, Tityus silvestris – found throughout the Amazon region – is considered of minor medical significance and with only a few descriptions in the literature. This article aims to describe for the first time the epidemiological characteristics and clinical manifestations of scorpion stings by T. silvestris that occurred in eastern Brazilian Amazon. Methods A prospective and observational study was carried out on 13 confirmed cases of T. silvestris envenomation registered from 2007 to 2011 in the cities of Belém and Ananindeua, Pará state, Brazil. Results The stings occurred mainly during daytime, at domiciliary environment, and the scorpions were found in clothing, fruits or vegetables. Envenomation was more frequent in the age group between 21 and 30 years old, upper limbs were more affected and medical aid was usually provided within two hours. Men and women were equally affected. Regarding severity, ten patients were classified as Class I and three patients as Class II according to the Scorpion Consensus Expert Group. Local manifestations were present in all patients, being pain the most common symptom. Mild systemic manifestations including nausea, vomiting, somnolence, malaise and prostration were observed in three victims. Symptomatic treatment of pain was offered to all patients, and only one received specific antivenom. All victims had a favorable outcome. Conclusions To the best of our knowledge, this study is the first to report the systemic symptomatology of envenomation by T. silvestris in the Brazilian Amazon, highlighting the medical relevance of the species in this region. Further research on the venom and clinical manifestations of envenomation by T. silvestris should be conducted in order to verify the relevance of this species to public health.